Respiratory Syncytial Virus Outbreak in the Basic Military Training Camp of the Republic of Korea Air Force - Won-Ju Park; Seok-Ju Yoo; Suk-Ho Lee; Jae-Woo Chung; Keun-Ho Jang; Jai-Dong Moon (Korean Society for Preventive Medicine, 2015)
Objectives: An outbreak of acute febrile illness occurred in the Republic of Korea Air Force boot camp from May to July 2011. An epidemiological investigation of the causative agent, which was of a highly infective nature, was conducted. Methods: Throat swabs were carried out and a multiplex reverse transcriptase-polymerase chain reaction (RT-PCR) assay was performed to identify possible causative factors. Results: The mean age of patients who had febrile illness during the study period was 20.24 years. The multiplex RT-PCR assay identified respiratory syncytial virus (RSV) as the causative agent. The main symptoms were sore throat (76.0%), sputum (72.8%), cough (72.1%), tonsillar hypertrophy (67.9%), and rhinorrhea (55.9%). The mean temperature was 38.75°C and the attack rate among the recruits was 15.7% (588 out of 3750 recruits), while the mean duration of fever was 2.3 days. The prognosis was generally favorable with supportive care but recurrent fever occurred in 10.1% of the patients within a month. Conclusions: This is the first epidemiological study of an RSV outbreak that developed in a healthy young adult group. In the event of an outbreak of an acute febrile illness of a highly infective nature in facilities used by a young adult group, RSV should be considered among the possible causative agents.